Cortona Young (online conference) - AAVV, AAVV (Il Colle di Galileo, 2021)
The e-Conference “Cortona Young”, hosted by the GGI on May 27-29, 2020, was set up as a response to the postponement of the 2020 edition of the Italian National Meetings “New Frontiers in Theoretical Physics - Convegno di Fisica Teorica di Cortona”, due to the COVID-19 pandemic. The conference was primarily addressed to young researchers, graduate students and postdocs connected with the Italian community of theoretical high energy physics. The aim was to give visibility to their most recent results in spite of the difficult situation for scientific exchanges. The program consisted of 12 live web-seminars, selected among over 50 applications, and of 24 video posters, made available through the GGI YouTube channel. The selected topics covered many different aspects of theoretical high energy physics, ranging from field and string theory to statistical mechanics, phenomenology and astroparticle physics. There were over 140 online participants, who were able to enter different virtual rooms for more focused discussion sessions. A special committee selected the best seminar, whose speaker was awarded a plenary talk in the next live edition of the Cortona meeting.